Aggressiveness Niche: Can It Be the Foster Ground for Cancer Metastasis Precursors?. (14th July 2016) - ElShamy, Wael M.; Sinha, Abhilasha; Said, Neveen
Abstract : The relationship between tumor initiation and tumor progression can follow a linear projection in which all tumor cells are equally endowed with the ability to progress into metastasis. Alternatively, not all tumor cells are equal genetically and/or epigenetically, and only few cells are induced to become metastatic tumor cells. The location of these cells within the tumor can also impact the fate of these cells. The most inner core of a tumor where an elevated pressure of adverse conditions forms, such as necrosis-induced inflammation and hypoxia-induced immunosuppressive environment, seems to be the most fertile ground to generate such tumor cells with metastatic potential. Here we will call this necrotic/hypoxic core the "aggressiveness niche" and will present data to support its involvement in generating these metastatic precursors. Within this niche, interaction of hypoxia-surviving cells with the inflammatory microenvironment influenced by newly recruited mesenchymal stromal cells (MSCs), tumor-associated macrophages (TAMs), and other types of cells and the establishment of bidirectional interactions between them elevate the aggressiveness of these tumor cells. Additionally, immune evasion properties induced in these cells most likely contribute in the formation and maintenance of such aggressiveness niche.